Replacing silkworms Tubifex sp. with fermented paste feed enriched with curcumin on Asian redtail catfish Hemibagrus nemurus larvae growth - Benny Heltonika; Netti Aryani; Nur Asiah; Indra Lesmana; Nuraini Nuraini; Firman Theodali Harefa (Jurnal Akuakultur Indonesia, 2026)
To maintain growth and survival, Asian redtail catfish postlarvae require silkworms as live food. However, due to their extreme sensitivity to natural conditions, silkworms will be exceedingly scarce during the rainy season. This study aimed to evaluate fermented commercial feed enriched with curcuminas replacement of silkworms for the growth and survival of redtail catfish postlarvae. This study employed a complete design experiment consisting of six treatments: P1 (non-fermented commercial feed), P2 (no curcumin-enriched fermented commercial feed), P3 (curcumin-enriched fermented commercial feed at 0.35 g/kg), P4 (curcumin-enriched fermented commercial feed at 0.70 g/kg), P5 (curcumin-enriched fermented commercial feed at 1.05 g/kg), and P6 (silkworms). Each treatment was replicated four times. The Asian red tail catfish postlarvae, measuring 0.63 ± 0.05 mm in length, were cultivated at a density of 5 fish/L. Fish were raised for a period of thirty days. Growth in total weight, total length, specific weight rate, specific length rate, and survival rate of postlarvae were the parameters measured. The growth evaluation results indicate that substituting silkworm feed with fermented feed supplemented with curcumin at a concentration of 1.05 g/kg resulted in growth of 6.66% (length) and 14.29% (weight) lower than the silkworm treatment (P<0.01). Despite this decline, it represents the most effective outcome in this study, highlighting the potential of fermented feed where enrichment with curcumin as an alternative to silkworms for Asian redtail catfish larvae nutrition. In conclusion, curcumin-enriched fermented feed can promote the growth of Asian redtail catfish postlarvae. Keywords: curcumin, fermented feed, growth, silkworm   Abstrak Untuk mempertahankan pertumbuhan dan kelangsungan hidup, postlarva ikan baung membutuhkan cacing sutra sebagai makanan hidup. Namun, cacing sutera sangat sensitivitas terhadap kondisi alam, cacing sutra akan sangat langka selama musim penghujan. Untuk mengganti cacing sutra, penelitian ini mengevaluasi pakan alternatif (pakan komersial terfermentasi yang diperkaya dengan kurkumin). Penelitian ini merupakan eksperimen dengan acak lengkap satu faktor yang terdiri dari enam perlakuan: yaitu P1 (Pakan komersial non-fermentasi), P2 (pakan komersial fermentasi yang diperkaya kurkumin), P3 (pakan komersial fermentasi yang diperkaya kurkumin pada 0,35 g/kg), P4 (pakan komersial fermentasi yang diperkaya kurkumin pada 0,70 g/kg), P5 (pakan komersial fermentasi yang diperkaya kurkumin pada 1,05 g/kg), dan F (cacing sutra). Setiap perlakuan diulang empat kali. Postlarva ikan baung, berukuran panjang 0,63 ± 0,05 mm, dibudidayakan pada kepadatan 5 ekor/L. Ikan dipelihara selama tiga puluh hari. Parameter yang diukur dalam penelitian ini adalah pertumbuhan berat total, panjang total, rata-rata pertumbuhan bobot, dan panjang spesifik serta kelulushidupan. Berdasarkan hasil evaluasi pertumbuhan menunjukkan pergantian pakan cacing sutera dengan pakan fermentasi yang diperkaya kurkumin 1,05 g/kg pakan menghasilkan pertumbuhan 6,66 % (panjang) dan 14,29% (berat) lebih rendah dari perlakuan cacing sutra (P<0,01), dan ini melrupakan hasil terbaik dari penelitian ini dalam upaya mencari pengganti pakan alternatif cacing sutera untuk postlarva ikan baung. Sebagai kesimpulan, pakan pasta terfermentasi yang diperkaya kurkumin dapat meningkatkan perkembangan postlarva ikan baung. Kata kunci: cacing sutera, kurkumin, pakan terfermentasi, pertumbuhan